Biosynthesis Of Silver Nanoparticles Using Marine Microalgae Isochrysis sp. - Tevan, R.; Saravanan, Jayakumar; Nor Haledah, Ahmad Sahimi; Nur Farah Ain, Iqbal; Iffah, Zapri; Natanamurugaraj, Govindan; Mohd Hasbi, Ab. Rahim; J. A. Ichwan, Solachuddin; Gaanty Pragas, Maniam (Universiti Malaysia Pahang, 2017)
Biosynthesis of metal nanoparticles has received a remarkable attention due to their eco-friendly and potential applications in pharmaceutical and medical fields. The searches for natural alternatives to replace biosynthetic nanoparticles have resulted in extensive studies of microalgal derived metal nanoparticles. Since there are very limited reports on Isochrysissp. in synthesising metal nanoparticles, a novel initiative was taken to induce an environmentally friendly and low cost technique to biosynthesise the silver nanoparticles (AgNPs) using marine microalgae, Isochrysis sp. Further, the synthesised silver nanoparticles were screened against human pathogen for antimicrobial effects. The characterisation of nanoparticles were confirmed by UV-visible spectroscopy, field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), and X-ray powder diffraction (XRD). The results obtained from characterisations indicate that the AgNPs have an almost spherical shape with a various size of 98.1 to 193 nm. The synthesised nanoparticles exhibited outstanding antioxidant and antimicrobial activities.